The status of Specific Language Impairment in Spanish-speaking countries - Andreu, Llorenç; Igualada, Alfonso; Ahufinger, Nadia; Sanz-Torrent, Mònica (Revista de Investigación en Logopedia, 2022)
Specific Language Disorder (SLI) is a developmental disorder that affects language expression and/ or comprehension. As a result of two studies with the Delphi methodology in English-speaking countries (Bishop et al., 2016; 2017), the use of the new terminology (i.e., Developmental Language Disorder or DLD) has become widespread, both in the clinical and educational field and in scientific publications, as well as the main agreements reached regarding its conception, identification, assessment, diagnosis, and treatment. A process of reflection by specialized experts in the field is necessary to analyze whether the adoption of the main agreements in the Anglo-Saxon context is feasible and adjusted for the Spanish-speaking contexts. The objective of this study is to analyze the status of developmental oral language in different Spanish-speaking countries regarding diagnostic labels, conception, diagnosis criteria and tools, as well as socioeconomic context, politics, and professional care. Data collection was done through a structured survey with open and closed answer questions (multiple choice and Likert scale) made to researchers and direct care professionals of the TEL from different disciplines (speech therapy, psychology, pedagogy, among others). The results show that the opinion of the participants on the main characteristics of the disorder, such as, the diagnostic label, conception, assessment, diagnosis, and treatment of this population in Spanish-speaking countries, as well as the discrepancies among them. The predominance of the SLI terminology stands out, although the use of the term DLD is increasing in use as a second label. The results also show great diversity in the diagnostic criteria and in some aspects of conception of the disorder. The current results provide relevant information about the particularities of the status of the disorder in Spanish-speaking countries regarding which can serve for a potential future consensus.
Keywords: Specific Language Impairment; SLI; Developmental Language Disorder; DLD; Spanish